Anionic ordering in Pb2Ti4O9F2 revisited by nuclear magnetic resonance and density functional theory. Issue 40 (23rd September 2022) - Oka, Kengo; Ichibha, Tom; Kato, Daichi; Noda, Yasuto; Tominaga, Yusuke; Yamada, Kosei; Iwasaki, Mitsunobu; Noma, Naoki; Hongo, Kenta; Maezono, Ryo; Reboredo, Fernando A.
Abstract : A combination of 19 F magic angle spinning (MAS) nuclear magnetic resonance (NMR) and density functional theory (DFT) were used to study the ordering of F atoms in Pb2 Ti4 O9 F2 . Abstract : A combination of 19 F magic angle spinning (MAS) nuclear magnetic resonance (NMR) and density functional theory (DFT) were used to study the ordering of F atoms in Pb2 Ti4 O9 F2 . This analysis revealed that F atoms predominantly occupy two of the six available inequivalent sites in a ratio of 73 : 27. DFT-based calculations explained the preference of F occupation on these sites and quantitatively reproduced the experimental occupation ratio, independent of the choice of functional. We concluded that the Pb atom's 6s 2 lone pair may play a role (∼0.1 eV per f.u.) in determining the majority and minority F occupation sites with partial density of states and crystal orbital Hamiltonian population analyses applied to the DFT wave functions.